Kedisiplinan Kerja Karyawan Untuk Peningkatan Kinerja (Studi Pengamatan Di PT. Tri Usaha Sejahtera Pratama) - LMS Kristiyanti (Jurnal Ilmiah Keuangan Akuntansi Bisnis (JIKAB), 2022)
Discipline is the key to the company's success in achieving its goals. Discipline is very important in improving employee performance, because with discipline all tasks will be completed properly and on time. Discipline also aims to make employees responsible for their work. Work regulations at PT TRUST apply to all employees without exception. So that all employees of PT TRUST must obey and comply with existing regulations. Sanctions given to employees for violations committed are in accordance with procedures. If the employee is unable to come to work, he must apply for a permit.